EX ANTE DAN EX POST PETANI YANG MENGONVERSI LAHAN DARI SAWAH KE PERKEBUNAN KELAPA SAWIT - Santi Minarti (Jurnal Saintifik (Multi Science Journal), 2022)
The purpose of this study was to determine the socio-economic impact of converting lowland rice farming land to oil palm plantations on ex ante (before) and ex ante (after) income conversion of farmers' land. This study uses qualitative data types from primary and secondary sources. The sample used was only farmers who did land conversion from lowland rice to oil palm plantations. Data were collected using an open questionnaire and the respondents were 20 farmers who converted their land. The data collection techniques used in this study were observation, interviews, documentation and questionnaires. The results of the study show that the decision of farmers to convert their paddy fields that they have is no longer productive for rice plants due to the abundant irrigation water that has now been reduced and has even gone dry. Ex post income of farmers who have converted land from rice fields to oil palm plantations can increase farmers' income. The existence of government policies will strengthen the causes of farmers' decisions to convert land, farmers think that their land cannot be used for rice fields anymore, so they convert their land to oil palm plantations so that they will be able to invest with long-term income. ABSTRAK Tujuan penelitian ini untuk mengetahui dampak sosial ekonomi dari konversi lahan pertanian padi sawah ke perkebunsn kelapa sawit terhadap pendapatan ex ante (sebelum) dan ex ante (sesudah) konversi lahan milik petani. Penelitian ini menggunakan jenis data kualitatif dari sumber primer dan sumber sekunder. sampel yang digunakan hanya petani yang melakukan konversi lahan dari padi sawah ke perkebunan kelapa sawit pengambilan data mengunakan kuisioner terbuka dan responden sebanyak 20 orang petani yang melakukan konversi lahan milik mereka. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah Observasi, Wawancara, Dokumentasi dan Kuisioner. Hasil penelitian menunjukan keputusan petani mengkonversikan lahan sawah yang petani miliki sudah tidak produktif untuk tanaman padi disebabkan oleh irigasi air yang melimpah sekarang sudah berkurang bahkan sudah kekeringan. Ex post pendapatan petani yang telah mengkonversi lahan dari sawah ke perkebunan kelapa sawit lebih dapat meningkatkan pendapatan petani. Adanya kebijakan pemerintah akan memperkuat penyebab keputusan petani untuk konversi lahan, para petani beranggapan daripada lahan yang mereka miliki tidak dapat dimanfaatkan lagi untuk sawah, jadi mereka konversikan lahan milik mereka ke perkebunan kelapa sawit dengan demikian mereka akan bisa investasi dengan pendapatan jangka panjang.